2019
DOI: 10.1097/md.0000000000015693
|View full text |Cite
|
Sign up to set email alerts
|

The biomarkers and potential pathogenesis of lung cancer related cerebral hemorrhage

Abstract: Cerebral hemorrhage is one of the common complications in patients with lung cancer (LC). Although cancer related cerebral hemorrhage was aware, the pathogenesis and biomarkers of lung cancer related cerebral hemorrhage (LCRCH) remained not well known. The aim of this study was to investigate the pathogenesis and plasma biomarkers of LCRCH. A retrospective review was conducted on acute cerebral hemorrhage patients with active LC who was admitted to the hospital between January 2007 and December 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…However, commonly used biomarkers, such as carcino-embryonic antigen and Cyfra21-1, offer low sensitivity and specificity and are not appropriate for clinical applications (3,4). Novel molecular or immunohistochemical-based biomarkers may facilitate identification of cancer at an early stage in the future (5). Therefore, there is a need for the development of novel markers.…”
Section: Introductionmentioning
confidence: 99%
“…However, commonly used biomarkers, such as carcino-embryonic antigen and Cyfra21-1, offer low sensitivity and specificity and are not appropriate for clinical applications (3,4). Novel molecular or immunohistochemical-based biomarkers may facilitate identification of cancer at an early stage in the future (5). Therefore, there is a need for the development of novel markers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that carcinoma mucins were overexpressed by malignant cells and were shown to play a multifaceted role in the initiation, progression, metastasis and subsequent colonization of multiple malignancies[ 27 , 28 ]. In a clinical study of lung cancer-related ICH, elevated plasma CEA and CA199 Levels were independent risk factors for ICH in patients with active lung cancer[ 13 ]. The researchers hypothesized that elevated cancer markers could activate platelets and lead to increased platelets, hypercoagulability, and eventually thrombotic events in the early stage of cancer; however, in the later stage, elevated cancer markers could lead to decreased platelets due to consumption, coagulopathy, and finally hemorrhagic events.…”
Section: Discussionmentioning
confidence: 99%
“…The National Institute of Health Stroke Scale (NIHSS) was used to evaluate the severity of focal neurological deficits. To minimize the effects of CRC progression on physical activities, patients’ functional prognosis on the 30th day after hemorrhage was measured using the modified Rankin Scale (mRS), and a mRS score > 3 was regarded as a poor prognosis[ 13 ]. According to a research study by Navi and colleagues on ICH[ 2 ], coagulopathy was identified if any of the following parameters were fulfilled: platelets < 100 × 10 9 /L, international normalized ratio (INR) > 1.5, activated partial thromboplastin time (APTT) > 45 s, prothrombin time (PT) > 15 s, and disseminated intravascular coagulation (DIC) (fibrinogen < 200 mg/dL and D-dimer > 290 ng/dL).…”
Section: Methodsmentioning
confidence: 99%
“…Tumor markers were detected in eight of the 23 patients, all of whom had one or more elevated tumor marker levels, which indicated that lung CT and tumor markers were necessary to improve the detection rate of combined lung cancer when the cause of intracerebral hemorrhage is unknown; previous studies have also shown that elevated plasma CEA and CA199 levels are associated with the pathogenesis of lung cancer related cerebral hemorrhage (LCRCH), and that the index derived from independent risks should serve as a specific biomarker of LCRCH. 26 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, according to the definition of coagulation dysfunction, 16 in this study, 12 of the 23 patients had coagulation dysfunction manifesting mainly as prolonged PT and elevated D-dimer levels, which is consistent with the findings of previous reports and suggests that thrombin dysfunction is a possible mechanism of tumor-related intracerebral hemorrhage. 14,26 Moreover, this indicates that abnormal coagulation may be the main cause of intracerebral hemorrhage in patients who do not have conventional vascular risk factors; however, coagulation dysfunction only accounts for a small proportion of common cerebral hemorrhage. 27 Some studies have shown that the most common causes of malignant tumor-related ICH may be intratumoral hemorrhage and abnormal coagulation, 10,16 and abnormal coagulation is usually caused by a variety of mechanisms, including abnormal platelet and abnormal coagulation factors.…”
Section: Discussionmentioning
confidence: 99%